Technical-pedagogical usability of digital inclusive reading support evolving through practice-to-research transfer - Junger, Ralf; Hanke, Judith (Frontiers in Education, 2025)
Reading competence is a prerequisite for academic success, yet studies reveal persistent deficits among primary school students, especially in inclusive classrooms. Digital formative diagnostics and aligned support tools offer promising opportunities; however, their sustainable implementation depends on both technical and pedagogical usability. This study explores the design of digital inclusive reading support to ensure usability and foster acceptance in practice. In the context of the collaborative project DaF-L, an adaptive digital reading screening and corresponding reading packages were developed and integrated into the competence-oriented learning platform Levumi as Open Educational Resources. A qualitative exploratory design was employed, integrating expert interviews with teachers (n = 13) and participatory classroom observations (n = 33) to capture perspectives from both teachers and students. Educators underscored the necessity for simplified navigation, individualized class management, and clear feedback mechanisms. The students’ positive response to motivational features, such as visual design, repetition opportunities, and immediate feedback, was noted. However, technical issues (e.g., unstable Wi-Fi connections, browser incompatibilities) and pedagogical challenges (e.g., skip function) were identified as factors that reduced usability. The findings indicate that the efficacy of digital formative reading support is contingent upon the synergy of intuitive technical design and pedagogical functionality, thereby facilitating differentiated learning. The study demonstrates how practice-to-research transfer can systematically enhance usability and provides implications for the future development of inclusive digital learning environments.